Corporate Governance in India - Issues and Challenges - Neelakantam, Tatikonda (Prabandhan: Indian Journal of Management, 2010)
The history of the development of Indian corporate laws has been marked by interesting contrasts. At independence, India inherited one of the world’s poorest economies, but one which had a factory sector accounting for a tenth of the national product; four functioning stock markets (predating the Tokyo Stock Exchange) with clearly defined rules governing listing, trading and settlements; a well-developed equity culture if only among the urban rich; and a banking system replete with well-developed lending norms and recovery procedures. In terms of corporate laws and financial system, therefore, India emerged far better endowed than most other colonies. The 1956 Companies Act as well as other laws governing the functioning of joint-stock companies and protecting the investors’ rights have been built on this foundation. Good corporate governance is characterized by a firm commitment and adoption of ethical practices by an organization across its entire value chain and in all of its dealings with a wide group of stakeholders encompassing employees, customers, vendors, regulators and shareholders (including the minority shareholders), in both good and bad times. To achieve this, certain checks and practices need to be whole-heartedly embraced.